Bioinformatics and genetic privacy: the impact of the Personal Data Protection Act 2010 - Abdul Ghani Azmi, Ida Madieha (Elsevier Advanced Technology, 2011)
Bioinformatics refers to the practise of creation and management of genetic data using computational and statistical techniques. In Malaysia, data obtained from genomic studies, particularly for the purpose of disease identification produces a tremendous amount of information related to molecular biology. These data are created from DNA samples obtained from diagnostic and research purposes in genomic research institutes in Malaysia. As these data are processed, stored, managed and profiled using computer applications, an issue arises as to whether the principles of personal data privacy would be applicable to these activities. This paper commences with an illustration of the salient features of the Personal Data Protection Act 2010. The second part analyses the impact of the newly passed Personal Data Protection Act 2010 on the collection of DNA sample, the processing of data obtained from it and the profiling of such data. The third part of the paper considers whether the various personal data protection principles are applicable to the act of DNA profiling and the creation of bioinformatics.